2022
DOI: 10.55672/hij2022pp136-219
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Gravity Emergence from Entanglement in a Multi-Fold Universe

Abstract: We start from a hypothetical multi-fold universe U_MF, where the propagation of everything is slower or equal to ‎the speed of light and where entanglement extends the set of paths available to Path Integrals. This multifold ‎mechanism enables EPR (Einstein-Podolsky-Rosen) “spooky actions at distance” to result from local interactions ‎in the resulting folds. It produces gravity-like attractive effective potentials in the spacetime, between entangled ‎entities, that are caused by the curvature of the folds. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
407
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(435 citation statements)
references
References 252 publications
28
407
0
Order By: Relevance
“…2.1 Neutrino Masses and Right-handed Neutrinos [1,5] observed that gravity induces chirality/ helicity flips for fermions, including the neutrinos. As no right-handed neutrino has ever been observed, it is assumed that right-handed neutrinos do not interact other than with the Higgs (and gravity) and so they appear only in flight as part of the neutrino oscillations.…”
Section: Reminder Of Past Results In Multi-fold Universesmentioning
confidence: 99%
See 2 more Smart Citations
“…2.1 Neutrino Masses and Right-handed Neutrinos [1,5] observed that gravity induces chirality/ helicity flips for fermions, including the neutrinos. As no right-handed neutrino has ever been observed, it is assumed that right-handed neutrinos do not interact other than with the Higgs (and gravity) and so they appear only in flight as part of the neutrino oscillations.…”
Section: Reminder Of Past Results In Multi-fold Universesmentioning
confidence: 99%
“…The new preprint [1] proposes contributions to several open problems in physics like the reconciliation of General Relativity (GR) with Quantum Physics, explaining the origin of gravity proposed as emerging from quantum (EPR-Einstein Podolsky Rosen) entanglement between particles, detailing contributions to dark matter and dark energy and explaining other Standard Model (SM) mysteries, without requiring New Physics beyond the Standard Model other than the addition of gravity to the Standard Model Lagrangian (i.e. now new forces or particles except for the notion graviton that deserves its own careful treatment).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that in a multi-fold universe, gravity increases at the scales of the Standard Model (something that we denote as SM G ) and we expected it to be non-negligible (even if small) with all the massive gravity contributions that start to contribute [12,20]. Accordingly, the microscopic radii involved are smaller than what is discussed in [19].…”
Section: Away From 2 As Landé G-factormentioning
confidence: 95%
“…Considering [7,8,12], the electron and the muon are modeled as microscopic black holes regularized by a superconducting edge that confines a condensate of massless Higgs boson inside. Even if surprising to many, this proposal recovers many results in physics e.g.…”
Section: Away From 2 As Landé G-factormentioning
confidence: 99%